2010
DOI: 10.1111/j.1399-3038.2010.01051.x
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal BCG vaccination induces IL-10 production by CD4+ CD25+ T cells

Abstract: To determine the optimal time of Bacillus Calmette-Guerin (BCG) vaccination for induction of Th1 immunity, we measured the interferon (IFN)-γ and interleukin (IL)-10 secretion in purified protein derivative (PPD)-stimulated peripheral blood mononuclear cell (PBMC) cultures in newborns vaccinated at birth or 2nd month of life. Moreover, role of CD4(+) CD25(+) T cells was studied by depletion assay at 8th month. Nineteen term and healthy newborns were randomized into two groups: Group I composed of 10 newborns v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 7 publications
2
16
0
1
Order By: Relevance
“…Recent studies showed that giving BCG vaccine at birth induces significant mycobacterial immune response as early as 2 months of life. When this response was tested at about 9 months of age it was found to be maintained and comparable to infants who received the vaccine at 2 or 4.5 months of life [12, 13]. …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that giving BCG vaccine at birth induces significant mycobacterial immune response as early as 2 months of life. When this response was tested at about 9 months of age it was found to be maintained and comparable to infants who received the vaccine at 2 or 4.5 months of life [12, 13]. …”
Section: Discussionmentioning
confidence: 99%
“…It is possible that priming with BCG induced T regs , which then dampened the induction of responses against LP-ESAT-6. It has been shown earlier that BCG vaccine triggers the specific activation of CD4 + and CD8 + T regs (43)(44)(45). However, to what extent the T regs affect boosting with another vaccine is not clear, and we did not evaluate them in our experiments as we performed all of our studies in mice with productive infection with Mtb.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, IL-10 also enhances antibody (Ab) production by promoting B-cell survival and differentiation and increasing the production of IgG4 Abs (13). IL-10 enhances generation of regulatory T cells (Tregs) that inhibit a neonatal immune response to BCG (16, 19). How elevated levels of IL-10 affect neonatal defense against other pathogens is unclear, but is likely context dependent.…”
Section: Cytokinesmentioning
confidence: 99%